The Integrated Farming Model Characteristics Of Maize And Cattle In Lima Puluh Kota Regency - Mukhlis Mukhlis (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to identify the characteristics of integrated maize and cattle farming. This research used a descriptive method, which was carried out in 50 Kota Regency. The choice of search area was made deliberately. Determination of the research sample using the snowball sampling method. Data collection used interview method using questionnaire to get primary data and documentation method to get secondary data. Data analysis methods use qualitative and quantitative descriptive analysis using triangulation techniques that test the accuracy of data through methods, sources and assumptions. The results show that the characteristics of corn and livestock integrated agricultural types include: 1) Corn crops have: Land area of ​​0.2-0.50 hectares, with land ownership and rent levels; seeds used by pioneers; Fertilizers used include: manure, compost, UREA, SP-36 and Ponska NPK; using grain waste in the form of leaves and sticks that are fed directly to livestock; 2) Characteristics of cattle, including: Simmental and Brahman cattle and a total of 2-5 cows; The products of cattle are calves, fodder, labor and medicine. The main ingredients of cow manure are: cow dung, leather, bran, EM-4, and sugar.